HUKUM SEBAGAI KESADARAN SOSIAL: KAJIAN ATAS PEMIKIRAN HUGO GROTIUS TENTANG DASAR UNIVERSALITAS HUKUM - Hendriyadi, Rato Eko; Adnan, Idul (PRODI HUKUM TATANEGARA, 2024)
Law is not merely a set of formal binding rules but also a reflection of society's social consciousness. Hugo Grotius, a philosopher and the father of international law, developed a theory on the universality of law rooted in human rationality and moral awareness. This article aims to examine Grotius' thoughts on law as a manifestation of social consciousness. Using a normative-philosophical approach, this study explores how Grotius' concept of universality of law serves as a foundation for harmonizing positive law with universal moral values. The study finds that law, according to Grotius, possesses universal characteristics as it is based on human reason, which is inherently social, rational, and moral. Thus, Grotius' theory remains relevant in the modern context to create more inclusive and just legal systems.